A retrospective study of etiology, clinical features, management, and outcomes in children with necrotizing pneumonia - Maaz Ahmed; K S Sanjay; M L Keshavamurthy; G V Basavaraja (Wolters Kluwer Medknow Publications, 2020)
Introduction: Necrotizing pneumonia (NP) is a severe and emerging complication in children with community-acquired pneumonia (CAP). The study was conducted to analyze the etiology, clinical features, treatment strategies, and outcome of NP in children admitted in a single pediatric tertiary referral care center. Materials and Methods: The study is a retrospective chart review which included children above 1 month and below 18 years who were admitted at Indira Gandhi Institute of Child Health, from January 2015 to December 2018, with community-acquired NP. Results: During the study period, 1393 cases of CAP were admitted in our institute. Three hundred and fifty-two cases (25.2%) of complicated pneumonia were admitted which include cases of NP, lung abscess, and empyema. Children who were diagnosed with NP were 3.3% (n = 46) of all CAP cases. All the cases with NP were immunocompetent, with the most common organism isolated being Staphylococcus aureus followed by Streptococcus pneumoniae. NP is associated with complications such as empyema, pneumothorax, and bronchopleural fistula. All the children in the study group survived except for mortality in one case. Conclusion: NP can be well managed with conservative approaches such as prolonged antibiotic therapy and pleural drainage. Although there are commonly associated with local complications, in general the clinical outcome is good.